SAKHAROV REMEMBERED : A Tribute by Friends and Colleagues - Drell, Sidney D., editor 272325; Kapitza, Sergei P., editor 302924 (New York, NY : American Institute of Physics, 1991)
"Blurb & Contents" Market: Physicists, astronomers, chemists, engineers, and graduate students. "Martin Bailyn's Survey is a marvelous resource for any teacher of thermal physics....The writing is clear; the references are extensive. If the textbook from which you are teaching leaves you dissatisfied with its treatment of a specific topic, Bailyn's compendium is a good place to look for a different or a deeper presentation." American Journal of Physics This work presents the application and theory of thermodynamics, including its formation according to statistical mechanics and its extension into Special Relativity. A unique feature of this book is the addition of the history of thermodynamics, designed to illustrate and emphasize the development of present day concepts. This book provides valuable insights into how these concepts evolved by discussing the pioneering work of Galileo, Clasuius, Kelvin, and others. The inclusion of both a complete survey of the subject, and an historical background (not found in other books) make this a valuable reference for individuals and graduate students.